Importance of tumor budding grade as independent prognostic factor for early tongue squamous cell carcinoma. Issue 6 (11th January 2019) - Ebihara, Yasuhiro; Yoshida, Saori; Nakahira, Mitsuhiko; Kogashiwa, Yasunao; Enoki, Yuichiro; Kuba, Kiyomi; Inoue, Hitoshi; Minami, Kazuhiko; Yasuda, Masanori; Sugasawa, Masashi
Abstract: Background: Factors involved in neck lymph node metastasis (NLM) and prognosis of early tongue squamous cell carcinoma (SCC) remain unknown. Methods: We analyzed disease‐specific survival (DSS) and NLM including tumor budding grade (TBG) among 64 patients with cT1/2N0 tongue SCC. Results: Univariate analysis of DSS of primary lesions uncovered significant differences in new cT, pT, new pT, pDiameter, venous infiltration, and TBG. Multivariate analysis selected only TBG3 as a predictor of NLM (odds ratio, 9.55; 95% confidence interval [CI], 1.80‐50.8; P  = .008), and a prognostic factor for DSS (hazard ratio, 4.41; 95% CI, 1.34‐14.5; P  = .02). Conclusion: The sole predictor of NLM and the prognosis of early tongue SCC was TBG, indicating that it might help to select overwhelming risk patients.